Disarming of autoreactive NK cells - Raulet, David (Henry Stewart Talks, 2009)
NK cell "education", NK cells in normal animals attack cells that lack some or all self MHC class I molecules, NK cells that lack inhibitory receptors for self MHC class I are rendered hyporesponsive and self tolerant, Hyporesponsiveness of NK cells is induced by target cells lacking MHC I, as in a mixed chimera, Responsiveness of NK cells varies depending on how many MHC I-specific receptors they express, NK cell education ensures that NK cells are optimally responsive yet not autoreactive